VALUE-ADDED TAX IN THE DIGITAL ECONOMY: A FRESH LOOK AT THE SOUTH AFRICAN DISPENSATION - Ruddy Kabwe; SP van Zyl (Obiter, 2021)
The online purchase of digital goods has the propensity to generate tax liability involving a notable rise in administrative costs for tax authorities. Online transactions involving the supply of digital goods by foreign businesses to South African consumers are subject to Value-Added Tax (“VAT”). Since 2014, the Value-Added Tax Act 89 of 1991 provides for registration and the reverse-charge mechanism as a means to collect VAT on online cross-border trade in digital goods. From 1 April 2019, significant changes to the VAT Act have been implemented regulating VAT on online cross-border trade in digital goods. This article examines these amendments by way of a comparative analysis of similar legislation in Australia and the European Union with the main aim of making recommendations for the adequate and cost-effective collection of VAT on online cross-border trade in digital goods.